Dancing with Hormones: A Current Perspective of Nitrate Signaling and Regulation in Arabidopsis - Guan, Peizhu (Frontiers in Plant Science, 2017)
In nature and agriculture, nitrate availability is a main environmental cue for plant growth, development and stress responses. Nitrate signaling and regulation are hence at the center of communications between plant intrinsic programs and the environment. It is also well known that endogenous phytohormones play numerous critical roles in integrating extrinsic cues and intrinsic responses, regulating and refining almost all aspects of plant growth, development and stress responses. Therefore, interaction between nitrate and phytohormones, such as auxins, cytokinins, abscisic acid, gibberellins, and ethylene, is prevalent. The growing evidence indicates that biosynthesis, de-conjugation, transport, and signaling of hormones are partly controlled by nitrate signaling. Recent advances with nitrate signaling and transcriptional regulation in Arabidopsis give rise to new paradigms. Given the comprehensive nitrate transport, sensing, signaling and regulations at the level of the cell and organism, nitrate itself is a local and long-distance signal molecule, conveying N status at the whole-plant level. A direct molecular link between nitrate signaling and cell cycle progression was revealed with TEOSINTE BRANCHED1/CYCLOIDEA/ PROLIFERATING CELL FACTOR1-20 (TCP20) - NIN-LIKE PROTEIN 6/7 (NLP6/7) regulatory nexus. NLPs are key regulators of nitrogen responses in plants. TCPs function as the main regulators of plant morphology and architecture, with the emerging role as integrators of plant developmental responses to the environment. By analogy with auxin being proposed as a plant morphogen, nitrate may be an environmental morphogen. The morphogen-gradient-dependent and cell-autonomous mechanisms of nitrate signaling and regulation are an integral part of cell growth and cell identification. This is especially true in root meristem growth that is regulated by intertwined nitrate, phytohormones, and glucose-TOR signaling pathways. Furthermore, the nitrate transcriptional hierarchy is emerging. Nitrate regulators in primary nitrate signaling can individually and combinatorially control downstream transcriptional networks and hormonal pathways for signal propagation and amplification. Under the new paradigms, nitrate-induced hormone metabolism and signaling deserve fresh examination. The close interplay and convergent regulation of nitrate and hormonal signaling at morphological, physiological and molecular levels have significant effects on important agronomic traits, especially nutrient-dependent adaptive root system growth and architecture.